2014
DOI: 10.18052/www.scipress.com/ilcpa.39.35
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Adsorption Capacity of Clay and Application in Dye Removal from Waste Water

Abstract: Natural clay has been considered as a potential absorbent for removing pollutants from water and waste water. Nonetheless, the effective application of clay for water treatment is limited due to small surface area and presence of net negative surface charge, leading to it low adsorption capacity. The absorption capacity was boosted via intercalation of CaO derived from snail shell (SS). The methylene blue sorption potential, PZC, and the surface area of unmodified clay sample were substantially enhanced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Results demonstrate that the particulate part of the organics is removed by the physical straining of the porous clay bricks surface whereas the dissolved organic component was expected to be removed via adsorption on to the surface of clay bricks. These results of the present study are in agreement with a pervious study that reported some sorption capabilities of natural clay for the removal of organics from wastewater [46]. The performance of the brick was found to be relatively poor for the removal of nutrients, i.e., 3.4%, 42.8%, 12.5%, 23.9 and 23.4%, removals for TN, NH 3 -N, NO 2 -N, and NO 3 -N, and PO 4 -P. Removal of some heavy metals including Mn, Cu, and Zn from stormwater was achieved whereas Ba and Cr were not removed during filtration.…”
Section: Stormwater Treatment Efficiencysupporting
confidence: 93%
“…Results demonstrate that the particulate part of the organics is removed by the physical straining of the porous clay bricks surface whereas the dissolved organic component was expected to be removed via adsorption on to the surface of clay bricks. These results of the present study are in agreement with a pervious study that reported some sorption capabilities of natural clay for the removal of organics from wastewater [46]. The performance of the brick was found to be relatively poor for the removal of nutrients, i.e., 3.4%, 42.8%, 12.5%, 23.9 and 23.4%, removals for TN, NH 3 -N, NO 2 -N, and NO 3 -N, and PO 4 -P. Removal of some heavy metals including Mn, Cu, and Zn from stormwater was achieved whereas Ba and Cr were not removed during filtration.…”
Section: Stormwater Treatment Efficiencysupporting
confidence: 93%
“…Therefore, the particulate portion of organics was removed by the physical straining of the micro-porous clay brick layer, whereas the dissolved organics portion was removed through adsorption onto the porous layers of the natural clay bricks. A previous study by Ogunmodede et al [37] also reported that natural clay possesses some sorption capability for organics in wastewater.…”
Section: Removal Of Organicsmentioning
confidence: 89%
“…Furthermore, higher organics (more than 75% of both BOD and COD) removals suggest that some portion of dissolved organics was also removed through adsorption on to the natural clay based ceramic filter used in this study. A previous study by Ogunmodede et al [52] also reported that natural clay has some sorption capabilities for organics from wastewater. The percentage removals for turbidity, TSS, and TDS presented in Table 3 are comparable with the other LID technologies [53,54].…”
Section: Removal Of Turbidity Tss and Tdsmentioning
confidence: 90%